ENVIRONMENTAL ETHICS: ISSUES AND SOLUTIONS - Reddy, T.Srikanth (International Journal of Psychosocial Rehabilitation, 2019)
Environment ethics is a critical study of the normative issues and principles relevant to the relationship between human and natural world. In this article I tried to find that on what ethical basis should we decide how to deal with nature . The main concern is that to which inherent value can be ascribed to things that are not human, including animals, vegetation, and even land. The integrated efforts are to be put so as to examine the interrelated components of environment system. Environmental ethics has much to contribute to the solution of global environmental problems and raise awareness about environmental problems. Human have a duty to act as benign stewards of the earth.